Forecasting A Long-Term Landslide Hazard in Paweden and Kalilunjar Sub-District, Banjarnegara, Indonesia - Lestari, Diah Valentina; Prasetyaningtiyas, Gayuh Aji (Dinamika Teknik Sipil: Majalah Ilmiah Teknik Sipil, 2024)
Climate change has been a global issue for the past decades. It has impacted numerous aspects in landslide, particularly in the slope stability. The soil mass rupture leads to damage to infrastructure and death. Thus, any prevention is urgently needed to minimize the risk.  Forecasting the hazards is part of disaster management. The Initial step of this action is forecasting the rainfall due to climate change for the next 20 years since 2010, given that most of the landslide hazards in Paweden and Kalilunjar are triggered by rainfall.  This study uses CORDEX-SEA to obtain the rainfall forecasting data as the input to simulate the slope stability. The rainfall seepage is performed to obtain slope safety factor by using Geo-studio. Two chosen sub-districts in Banjarnegara, Paweden and Kalilunjar, are expected to experience more extreme daily rainfall by the end of 2030 compared to 2010 conditions. This study also shows that all rainfall cases trigger a slope failure (FS<1.2). This study is expected to support the local government in deciding the next hazard mitigation plan.